Baklava Dessert House / Elsie Gotisin Sudang ... [et al.] - Gotisin Sudang, Elsie; Saadon, Fadhlin; Abduk Razak, Razwin; Zainuddin, Rosmawati (Faculty of Architecture, Planning & Surveying, 2003)
Our registered business is Baklava Dessert House. It will start operating on December 2003. Baklava Dessert House. Is established on the main purpose to cater the shortages of the dessert cafe type. We finally agreed to set cafe because it has change to attract people. Our location is at Lot A13, Giant Hypermarket Section 13, Persiaran Sukan Shah Alam, Selangor Darul Ehsan. It is the best area to run the business. The location is near by the university, Giant Hypermarket, Macro world wide, PTPL College, Shah Alam Stadium, Batu Tiga Speed Way (BTSC), Business Center and residential areas. Our target customer would be office workers, lecturers and student who stayed in a variety. The special dishes for an example cappuccino, pudding cakes and drinks also our very own trademark the baklava juice are cook and made by the local chefs who expertise with all those dishes. We had carried out studies on the catchments area or customer's behavior for our state projection per year. We realized that the customer prefer to have good and efficient services. There also prefer a clean and tidy cafe with friendly workers. The special and delicious dishes also intend the customers to come again to our cafe. We have to maintain this kind of strategies in order to keep and increase the number customers.